RAGE inhibition reduces acute lung injury in mice - Raiko Blondonnet; Jules Audard; Corinne Belville; Gael Clairefond; Jean Lutz; Damien Bouvier; Laurence Roszyk; Christelle Gross; Marilyne Lavergne; Marianne Fournet; Loic Blanchon; Caroline Vachias; et al. (Scientific Reports, 2017)
Abstract The receptor for advanced glycation end-products (RAGE) is involved in inflammatory response during acute respiratory distress syndrome (ARDS). Growing body of evidence support strategies of RAGE inhibition in experimental lung injury, but its modalities and effects remain underinvestigated. Anesthetised C57BL/6JRj mice were divided in four groups; three of them underwent orotracheal instillation of acid and were treated with anti-RAGE monoclonal antibody (mAb) or recombinant soluble RAGE (sRAGE), acting as a decoy receptor. The fourth group served as a control. Lung injury was assessed by the analysis of blood gases, alveolar permeability, histology, AFC, and cytokines. Lung expression and distribution epithelial channels ENaC, Na,K-ATPase, and aquaporin (AQP)−5 were assessed. Treatment with either anti-RAGE mAb or sRAGE improved lung injury, arterial oxygenation and decreased alveolar inflammation in acid-injured animals. Anti-RAGE therapies were associated with restored AFC and increased lung expression of AQP-5 in alveolar cell. Blocking RAGE had potential therapeutic effects in a translational mouse model of ARDS, possibly through a decrease in alveolar type 1 epithelial cell injury as shown by restored AFC and lung AQP-5 expression. Further mechanistic studies are warranted to describe intracellular pathways that may control such effects of RAGE on lung epithelial injury and repair.